MENGOPTIMALKAN PERAN RADIO KOMUNITAS SEBAGAI RUANG PUBLIK & MEDIA INTERAKSI KOMUNIKASI LINTAS PEMANGKU KEPENTINGAN (Studi pada Radio Komunitas Denta FM Sumbermanjing Kulon Kecamatan Pagak dan RadioJaya FM Mendalan Wangi Kecamatan Wagir Kabupaten Malang) - Eko Agus Susilo (Universitas Merdeka Malang, 2016)
Abstract Unlikethe private radio whoseprimary interests is reaping economic profitatthe expense of orginalizing other social benefit, community radio is the one that is owned, managed by, from and for thecommunity’swellbeing. It isalocal,low-power broadcasting specifically designed for serving the entire interest of community members. Itputs audiences’ cultural identity development at it stoppriority. Unfortunately, thisi deal never materialize due to its poor human resources quality in managing the radio station and producing on-air radio program as well as its broadcaster ’sinadequate announcing skills especially with regard to broadcasting code of conduct. To makething even worst, its on-air program broadcast operates exclusively for the owner’s interest and meeting its restricted fansclub members. As such, its daily on-air radio content program does not take the people’s interest into consideration.It does not involve its other stakeholders such as village government apparatus, prominent leaders, and its faithfull isteners inboth radio management as well as radio program broadcasting development. To help solve the problem, this Ibm project have designed as aseries of capacity building methods by mean so inclass training as well as on the job clinic coaching for community radio staffs and practicing ads production at Communication Department Laboratory. The training module coverson-airradio broadcasting codeof conduct, announcing skills, spot advertising and radio program production. To facilitate their capacities building, the project has granted aset of technical devices such as digital voice recorder and station transmitter link. Like wise,it trained radio community stakeholders on matters such as the definition, regulation of community radio along with ideal organizational structure which was solely aimed at having them participatein operating radio management. There search found that after capacity building intervention activities, the radio personnel program broadcasting skills has improved significantly. Similarly, the stakeholders’ skills have also increased. Seeing from this, radio community canoperate as villagers public sphere; anarena for deliberating on matters on common concerns and then reachinga consensus of the problem for their sole future betterment. Keywords: Community Radio, Public Sphere, Participation, Radio Program Broadcasting Development Skills,Community Empowerment DOI : https://doi.org/10.26905/nomosleca.v2i1.377